Foreign banks increase the social orientation of Estonian financial sector - Mart S\~org; Danel Tuusis (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2008)
Reconstruction of Estonian banking system started twenty years ago. Estonia built up for the market economy a banking oriented financial sector, which is centred on commercial banks. During the two decades less than ten banks remained from more than 50 licensed commercial banks, the rest were not able to continue independently, they merged or have failed. The bad result of such kind of development was also the excessive concentration of banking. Banking sector in Estonia during the transition period was opened to the invasion of foreign banks due to the openness of the economy and excessive risks taken. Two banking crises, selected quickly the very limited number of prosperous banks, and the major commercial banks went into the ownership of Scandinavian banks. The qualitative effects of foreign banks' entry into the Estonian banking market were new features of competition in banking market and transfer of various knowhow from foreign banks. Better liquidity risk management techniques, information systems, credit policy and personnel policy transfer from foreign banks supported banks to have high profitability and low credit losses rates. These directions are noticeable also by quantitative analyses of banking market development. The takeover of main commercial banks by the large Swedish and Finnish banks was one of important factors in the gradual increase of the social orientation of Estonian banks however the ideas of social responsibility of enterprises are especially popular in Scandinavia. In our paper we analyse also Estonian banks' practices of supporting the social development of Estonia.
Keywords: 330; Internationale Bank; Markteintritt; Corporate Social Responsibility; Bank; Estland